Diseño y construcción de dos módulos asistidos por microcontroladores para la medición de magnitudes físicas de temperatura y desplazamientos en función del tiempo en experimentos de laboratorio - Minez Cuba, Yamil Zenefelder (2012)
Knowing the advantages microcontrollers provide (programmable integrated_x000D_ circuits and control) as they are resources, reliability, versatility, speed, price_x000D_ etc.. I can make electronic design, build and launch them at a low price and_x000D_ good quality._x000D_ To design this module was used one of the most versatile and cheap_x000D_ microcontrollers on the market, the Microcontroller PIC16F877A, which was_x000D_ designed with this module and whose function is to make measurements for a_x000D_ range of time for two events kinematic motion and store in the internal memory_x000D_ and then visualize on an LCD processing according to the program in the_x000D_ microcontroller, also introduced a program to measure temperature and apply to_x000D_ the concepts of the universal law of gases in thermodynamic processes._x000D_ The results of these experiments prove possible to corroborate laws and_x000D_ equations of various physical topics, and most importantly motivating students to_x000D_ analyze in more detail each physical phenomenon that they can experience in_x000D_ these modules, the same student will generate new applications for the use of_x000D_ these modules